Don't forget the below-ground crops: introducing sweet potatoes into the concept of digital agriculture - Oliveira, Danilo Tedesco de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
To produce quality food to meet global demand amidst climate uncertainty with sustainable management practices is one of the major challenges of the coming decades. If we truly want to meet this demand, digital tools are the key to making food production safer. However, efforts to develop such tools are entirely focused on the crops of greatest commercial interest, while leaving aside crops of minor interest, such as below-ground crops. Most below-ground crops are grown by smallholder’s farmers. These farmers do usually do not have the necessary resources or knowledge to develop or adapt these tools to their needs. Due to the importance of these crops' nutritional value in day-to-day diets, in this dissertation we show that we cannot forget below-ground crops. To contribute to the solution of this problem, we developed methods to assess the pattern of growth, yield, and quality of sweet potatoes. We show that weather and satellite data can be used to detect some changes in growth stages and predict crop traits. Our efforts introduce the sweet potato crop in the current context of e-farming agriculture.

Produzir alimentos de qualidade para atender a demanda global, em meio as incertezas clim ` aticas com pr ´ aticas de manejo sustent ´ aveis ´ e um dos maiores de- ´ safios das proximas d ´ ecadas. Se realmente queremos atender a essa demanda, as ´ ferramentas digitais sao a chave para tornar a produ ˜ c¸ao de alimentos mais segura. ˜ No entanto, os esforc¸os para desenvolvimento dessas ferramentas estao totalmente ˜ focados para as culturas de maior interesse comercial, deixando de lado as de menor interesse, como as culturas subterraneas. Grande parte das culturas subterr ˆ aneas ˆ sao cultivadas por pequenos produtores rurais. Eles n ˜ ao possuem recursos ou con- ˜ hecimento necessarios para desenvolver ou adaptar essas ferramentas para suas ´ necessidades. Devido a importancia do seu valor nutricional na alimenta ˆ c¸ao di ˜ aria, ´ nesta tese mostramos que nao podemos esquecer das culturas subterr ˜ aneas. Para ˆ contribuir com a soluc¸ao desse problema, n ˜ os desenvolvemos m ´ etodos para avaliar o ´ padrao de crescimento, produ ˜ c¸ao e qualidade da batata-doce. Mostramos que dados ˜ de clima e de satelites podem ser usados para detectar mudan ´ c¸as em estagios de ´ crescimento e predizer caracter´ısticas da cultura. Nosso trabalho introduz a cultura da batata-doce no contexto atual da agricultura conectada.
Não esqueçam das culturas subterrâneas: introduzindo a batata-doce no contexto da agricultura digital
Keywords: Remote sensing; Agriculture; Harvesting; Yields; Batatas